Stabilization policy: A turbulent journey through time - Oliver Landmann (University of Freiburg, Department of International Economic Policy (iep), 2022)
The theory and practice of stabilization policy has taken many turns as it evolved over the past century, oscillating between high hopes and deep skepticism regarding the capacity - and desirability - of governments taking responsibility for macroeconomic stability. This paper reviews the turbulent history of stabilization policy, highlighting the close interaction between events, policies, and ideas. The focus is on the single most debated issue in this history: the resilience of a market economy in the face of macroeconomic shocks. Views on this question have been shaped by experience, theory and ideology to varying degrees.
Keywords: B10; B20; E00; E32; E50; E62; 330; Stabilization Policy; Macroeconomics; Fiscal Policy; Monetary Policy; History of Economic Thought